On the Limits of CALIOP for Constraining Modeled Free Tropospheric Aerosol. Issue 17 (6th September 2018) - Watson‐Parris, Duncan; Schutgens, Nick; Winker, David; Burton, Sharon P.; Ferrare, Richard A.; Stier, Philip
Abstract: The spaceborne Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) instrument provides valuable information on the vertical distribution of global aerosol and is often used to evaluate vertical aerosol distributions in general circulation models (GCMs). Here we show, however, that the detection limit of the CALIOP retrievals mean background aerosol is not detected, leading to substantially skewed statistics that moreover differ significantly by product. In the CALIOP Level 2 product this missing low‐backscatter aerosol results in the retrieved aerosol distribution significantly overrepresenting aerosol backscatter and extinction in the middle and upper troposphere if taken to be representative of the undetected aerosol. The CALIOP Level 3 product assumes no aerosol where none is detected, which then leads to an underestimation in the aerosol extinction profile in the upper troposphere. Using the ECHAM‐HAM GCM, we estimate that the mean fraction of aerosol undetected by CALIOP daytime (nighttime) retrievals is 41% (44%) globally. Plain Language Summary: The spaceborne Cloud‐Aerosol Lidar with Orthogonal Polarization (CALIOP) instrument provides valuable information on the vertical distribution of global aerosol and is often used to evaluate vertical aerosol distributions in general circulation models (GCMs). Here we show, however, that the detection limit of the CALIOP retrievals mean background aerosol is not detected, leading to substantially skewed statistics that depend on assumptions about the missing aerosol. Using the ECHAM‐HAM GCM, we estimate that the mean fraction of aerosol undetected by CALIOP daytime (nighttime) retrievals is 41% (44%) globally. Key Points: Current CALIOP data products are shown to provide only an upper bound on modeled aerosol concentrations in the free troposphere The practice of filling in missing retrievals has a disproportionate effect in the free troposphere where most aerosol is undetected